«Peaceful Atom» – from the XXth to the XXI century: from the weapons of mass destruction to the driver of the massive progress - M. V. Zharkikh (Vestnik MGIMO-Universiteta)
The article is dedicated to the progress-analysis of the development of one of the most promising fields of economy and industry of Russia as well as many other states of the world – the atomic energy sector. Its evolution and competitive advantages before the other sources of energy supply are attended in brief. Special attention is devoted to international cooperation in the atomic energy field, incentivized at the beginning of the XXI century. Dynamics of this cooperation has shown that atomic energy can and, most probably, in the nearest future, will become one of the main factors of an advanced socioeconomic development of most of the states.